Pre-service Teachers’ Noticing of 7th Grade Students’ Errors and Misconceptions about the Subject of Equations - Seval Deniz Kılıç (Sakarya University Journal of Education)
Teachernoticing is one of the issues that math educators have given importancerecently. The noticing-raising skills that require a professional vision beyondtheir use in daily life requires a series of activities within the framework ofprior learning by the teacher, then interpreting and providing appropriatefeedback. Investigating the level of awareness in pre-service teacher traineeswill provide a foresight for future education. In the field of algebralearning, it has been identified in previous studies that primary schoolstudents experience various misconceptions and have a trouble. Therefore, theaim of this study is to determine the misconceptions and errors of 7th gradestudents about equations and to observe their noticing of these errors andmisconceptions. Participants of the study, in which qualitative researchmethods have been adopted, are 3 student and 3 mathematics teacher candidateswith medium and high academic achievement. As a means of data collection, inthe scale of error and misconceptions about equations was utilized and teachercandidates' awareness of these responses was investigated. At the end of thestudy, it was found that the success of the attending step was not sufficientfor the other steps.